2019
DOI: 10.1177/0731684419858187
|View full text |Cite
|
Sign up to set email alerts
|

Size sensitivity of residual stress and deformation in co-curing process of T-stiffened composite skin assembly

Abstract: The stiffener plays an important role in the overall performance of T-stiffened skin assembly which is a primary structure of aircraft. In this paper, a thermo-viscoelastic finite element model that has been verified by experimental results was established to investigate the effect of the stiffener on stress concentration, stress redistribution, and deformation of T-stiffened skin assembly during curing. The size dependence of residual stress and deformation was analyzed by establishing a series of integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Extensive efforts have been invested to address PID problems using empirical science, 5‐8 theoretical science, and computational science methods 9‐17 . The most commonly used theoretical models of the finite element method (FEM) proposed previously include the elastic model, 10,11 cure‐hardening instantaneously linear elastic (CHILE) model, 12 path‐dependent model, 13 and viscoelastic model 14,15 . Furthermore, Galinska 16 reported a comparative study for PID simulation; the results for which indicated that the difference between the elastic and theoretically more precise CHILE models is very small.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive efforts have been invested to address PID problems using empirical science, 5‐8 theoretical science, and computational science methods 9‐17 . The most commonly used theoretical models of the finite element method (FEM) proposed previously include the elastic model, 10,11 cure‐hardening instantaneously linear elastic (CHILE) model, 12 path‐dependent model, 13 and viscoelastic model 14,15 . Furthermore, Galinska 16 reported a comparative study for PID simulation; the results for which indicated that the difference between the elastic and theoretically more precise CHILE models is very small.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately describe the change of composite mechanical properties during curing, different constitutive models were proposed in numerical models. These constitutive models can be simply divided into three types: elastic [ 6 , 7 ], viscoelastic [ 8 , 9 , 10 , 11 , 12 , 13 ] and simplified viscoelastic models [ 14 , 15 , 16 , 17 , 18 ]. The cure hardening instantaneously elastic constitutive model proposed by Bogetti et al [ 6 ] is a typical linear elastic model, which assumes that the resin modulus increases linearly with the cure degree.…”
Section: Introductionmentioning
confidence: 99%